Continuing education in biochemistry and molecular biology in industry: A parallel session at the IUBMB/PSBMB 2019 "Harnessing Interdisciplinary Education in Biochemistry and Molecular Biology" conference. Issue 6 (19th October 2020) - Chuang, Woei‐Jer; Concepcion, Gisela P.; Lin, Huixin; Yu, Gracia Fe B.; Macaulay, Janet
Abstract: Science requires that we are always current with research, techniques, and tools but what are the best approaches for continuing education? The presenters in this session described a range of approaches used in universities, government bodies, and industry.